The Relationship between Bullying Behavior and Students' Social Interaction Ability - Khairul Anwar; Yeni Karneli (Universitas Negeri Padang, 2020)
Social interaction is a dynamic reciprocal social relationship, which involves the relationship between individuals as individuals, between human groups, or between people and human groups. Good social interaction can prevent bullying behavior. Bullying is a form of violent behavior where there is psychological or physical coercion on a person or group of people who are